Cognitive impairment in Japanese patients with multiple sclerosis: Are social activities affected by cognitive impairment?. Issue 3 (October 2014) - Nakatsuji, Yuji
Abstract A large proportion of patients with multiple sclerosis (MS) show cognitive impairment. Multiple sclerosis tends to affect people in their productive years. Niino et al. reported the associations of cognitive impairment with magnetic resonance imaging findings and social activities in Japanese patients with multiple sclerosis.